Identifying surge of exclusionary nationalism: A case study of prewar Japan - Tomoko Matsumoto; Yutaka Shimada; Hiroyuki Hirate; Tohru Ikeguchi (PLoS ONE, 2026)
A rise in exclusionary nationalism can escalate conflicts; however, there are limited quantitative analyses of the timing and magnitudes of such shifts. This study proposes a quantitative approach for tracking changes in exclusionary nationalism by focusing on language, specifically the acceptance/rejection of foreign loanwords. Using 300,110 Japanese newspaper articles spanning 1912–1943—the period surrounding the outbreak of the 1941 conflict with the United States and the United Kingdom—we employed the singular spectrum transformation method to detect change points in exclusionary nationalism. We found that exclusionary nationalism emerged in Japan in 1936 and subsequently exhibited substantial oscillations rather than continuous intensification in the years leading up to the outbreak of the Pacific War. Moreover, attitudes toward potential adversaries and allies were evident from the 1920s. This study deepens our understanding of the role of exclusionary nationalism in conflicts, highlighting its nuanced nature in shaping friend–enemy distinctions during wartime.